Extensive physiologic melanin pigmentation on the tongue: An unusual clinical presentation - Chandra, Sunira (Medknow Publications Pvt Ltd, 2010)
Pigmented lesions are commonly found in the oral cavity. Pigmentation has a multifactorial etiology. Most of the oral pigmentations are physiologic but sometimes it can be a precursor of severe diseases. Evaluation of a patient presented with a pigmented lesion should include a full medical and dental history, extraoral and intraoral examinations and even in some cases biopsy and laboratory investigations are required. In this article, we report a case of extensive physiologic pigmentation on the tongue in a 32-year-old female patient, posing a diagnostic challenge.